A new patch antenna for ultra wide band communication applications - Anwar Sabah; Malik Jasim Farhan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A printed monopole patch Ultra Wide Band (UWB) antenna for use in UWB application is proposed in this paper. The proposed antenna consists of a patch with appropriate dimensions on one side of a dielectric substrate, and a partial ground plane on the other side of the substrate. The techniques that used to enhance the bandwidth are the partial ground plane, feed point position and adjusted feed gap. The substrate that is used in the proposed antenna is Fr4 epoxy, the optimum dimensions of the antenna are 40mm×28mm×1.5mm this antenna designed by HFSS program. The band achieved by the proposed antenna is from 3.6GHz to 15GHz. This antenna is fabricated in the ministry of science and technology Baghdad-Iraq and a good agreement between simulation and measured S11 is achieved.